2019–2020 Florida Citrus Production Guide: Canopy Management - Tripti Vashisth; Mongi Zekri; Fernando M. Alferez (EDIS)
Tree canopy and bearing volume are two important factors in fruit production and fruit quality. Generally, trees with larger canopy and bearing volumes produce more fruit than smaller-canopy trees. Canopy management is an important aspect of citrus production in Florida to avoid problems associated with overcrowding and excessively tall trees, to improve light interception, and to improve pesticide distribution into the canopy as well as to facilitate equipment operation within the grove. Proper control of vegetative growth is essential for the maintenance of healthy, productive citrus trees. This 4-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Tripti Vashisth, Mongi Zekri, and Fernando M. Alferez. and published by the Horticultural Sciences Department, March 2019.